A Case Report of EGFR-TKIs Resistant Secondary MET Gene Amplified Lung Squamous Cell Carcinoma and Literature Review - Yalan LIU; Peng CHEN; Xinfu LIU (Chinese Journal of Lung Cancer)
With the rapid development of epidermal growth factor receptor (EGFR) gene testing of lung adenocarcinoma patients has been routinely carried out, EGFR mutations are also possible for some small samples of non-smoking female lung squamous cell carcinoma patients. This increases the opportunity for targeted therapy for this group of patients. However, drug resistance in patients with lung squamous cell carcinoma during targeted therapy is an important factor affecting subsequent treatment. There are multiple mechanisms of acquired drug resistance in targeted therapy, and the alteration of mesenchymal-epithelial transition factor (MET) signaling pathway is one of the common mechanisms of drug resistance. At present, some selective tyrosine kinase inhibitors (TKIs) of MET has been approved for non-small cell lung cancer with MET gene 14 exon skipping mutation, such as Glumetinib, Savolitinib, Tepotinib, Capmatinib, etc. Drugs that target secondary MET amplification are still in clinical trials. This paper retrospectively analyzed the clinical data of a female patient with EGFR-TKIs resistant secondary MET amplified squamous cell lung cancer, and reviewed relevant literature to explore how to optimize the treatment of lung squamous cell carcinoma patients with EGFR mutation, so as to provide clinical reference for the diagnosis and treatment of such patients.